2006
DOI: 10.4141/a05-092
|View full text |Cite
|
Sign up to set email alerts
|

Review: The composition and availability of straw and chaff from small grain cereals for beef cattle in western Canada

Abstract: . 2006. Review: The composition and availability of straw and chaff from small grain cereals for beef cattle in western Canada. Can. J. Anim. Sci. 86: 443-455. Small cereal grain residues are heterogeneous feeds consisting of several botanical fractions: chaff, grain, leaf blade, leaf sheath, internode and node. These parts vary in composition, digestibility, resistance to comminution, intake potential and energy availability. Large differences in the nutritional quality of straw and chaff may occur from year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…In our calculations the rye grain to straw ratio wass 2/1 [58]. Table 6 shows that diesel oil for transportation, seeds production and the chemical fertilizers are the largest energy consumers in agriculture.…”
Section: Modeling Of Agriculture and Bread And Bun Making Processesmentioning
confidence: 99%
“…In our calculations the rye grain to straw ratio wass 2/1 [58]. Table 6 shows that diesel oil for transportation, seeds production and the chemical fertilizers are the largest energy consumers in agriculture.…”
Section: Modeling Of Agriculture and Bread And Bun Making Processesmentioning
confidence: 99%
“…Kaliel and Kotowich (2002) reported that winter feeding of beef cows represents 60Á65% of the total cost of production in a Canadian cow/calf operation [as reported by McCartney et al (2006)]. There may be opportunities to keep winter feeding costs low by utilizing lower quality and lower cost forages, such as crop residues from grain corn and cereal grains.…”
mentioning
confidence: 99%
“…Cereal straws in particular have been extensively studied as a low cost winter feedstuff for beef cows (Tellier et al 2004;McCartney et al 2006). Much of the research has focused on additives and treatments of straws to improve nutritive value and digestibility by processes such as ammoniation (Males 1987).…”
mentioning
confidence: 99%
“…Wheat straw is an effective feedstuff for use in wintering beef cows, particularly in western Canada (McCartney et al 2006). Since wheat straw alone is low in CP and high in neutral detergent fibre and acid detergent fiber (ADF), digestibility and voluntary intake can be relatively low (Males 1987).…”
mentioning
confidence: 99%
“…Crop residues may provide up to 50 to 60% of dry matter intake (DMI) needed to maintain the pregnant beef cow over winter (McCartney et al 2006); however, an additional nutrient source is needed to meet the requirements for energy and crude protein (CP), prevent rumen impaction, maintain DMI, improve digestibility and increase performance (Pritchard and Males 1982;Wiedmeier et al 1983;Pritchard and Males 1985;Bohnert et al 2002;Tellier et al 2004). The impact of nutrition on the pre-partum performance of the cow must be considered in any winter feeding program, since poor pre-partum nutrition can negatively impact the growth and development of the conceptus [National Research Council (NRC) 1996].…”
mentioning
confidence: 99%